Design of Bionic Bird Jumping Mechanism for Autonomous Take-off and Landing Based on the Micro-platform - Zhang Chunpeng; Shao Weiping; Hao Yongping (Jixie chuandong)
Aiming at the function of the lower limb of bionic flapping birds, the lower limb bounding mechanism is studied. Based on the size ratio of the lower limb bone of birds, the lower limb movement characteristics of birds are analyzed. In order to avoid the interference between the wings and the ground in the jumping squat stage, the lower limb jumping mechanism is designed based on the micro-platform take-off and landing method. In order to improve the imitation of lower limbs, a parallelogram like lower limb leg mechanism is designed, and the kinematic equation of lower limb mechanism is established by combining the spatial D-H expression method. Based on the Lagrange equation, the dynamic equation of the lower limb mechanism is established. Adams software is used to simulate the bouncing of the assembly, and the lower limb and leg mechanism are solved. The results show that the initial velocity of the assembly body core level reaches the critical speed condition required for the goshawk take-off, and it can realize the bouncing take-off.